Alternative Water Source: Concept of Atmospheric Water Generator using Wet Desiccation Method - Poudel, Anup Jwala; Subedi, Achyut; Shah, Amar; Chhetri, Amisha; Bhandari, Kritika; Kishor, Shacheendra (Journal of Engineering and Sciences, 2022)
Abstract available with the full text.